2017
DOI: 10.1016/j.snb.2016.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polypyrrole decorated graphene/β-cyclodextrin composite for low level electrochemical detection of mercury (II) in water

Abstract: Mercury (Hg(II)) is considered as one of the most toxic element that directly affects the human health and the environment. Therefore, in this study, we propose a sensitive and disposable electrochemical sensor for the detection of Hg(II) in various water samples using polypyrrole (PPy) decorated graphene/β-cyclodextrin (GR-CD) composite modified screen-printed carbon electrode (SPCE). The GR-CD/PPy composite was synthesized by chemical oxidation of PPy monomer in GR-CD solution using FeCl3. Differential pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Ppy can also be used as a catalytic support in electrochemical fuel cells, drug delivery, sensors, and batteries. 13,14 Electrochemically prepared polypyrrole/chitosan composites have already been reported for applications as electrochemical biosensors and anti-corrosive coatings, 15 and also applied as surface protective agents to improve the performance of 316L SS bio-implants, as reported by Kumar et al 16 With regards to photocatalytic activity, polypyrrole exhibited a synergistic effect with ZnO to enhance the activity of the photocatalyst by minimizing the recombination behaviour of the charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Ppy can also be used as a catalytic support in electrochemical fuel cells, drug delivery, sensors, and batteries. 13,14 Electrochemically prepared polypyrrole/chitosan composites have already been reported for applications as electrochemical biosensors and anti-corrosive coatings, 15 and also applied as surface protective agents to improve the performance of 316L SS bio-implants, as reported by Kumar et al 16 With regards to photocatalytic activity, polypyrrole exhibited a synergistic effect with ZnO to enhance the activity of the photocatalyst by minimizing the recombination behaviour of the charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the binding of Hg(II) to PPy is through the nitrogen atoms of the PPy. The lone pair of electrons on the nitrogen atom can bind with the Hg(II) without difficulty . However, the GCE/PPy stripping current was lower than GCE/PPy/S‐IIPs because of the predetermined active sites of the S‐IIPs on the surfaces which had more affinity for the Hg(II), therefore more Hg(II) could be accumulated and reduced to Hg(0).…”
Section: Resultsmentioning
confidence: 99%
“…In the electrochemical detection of Hg(II), various electrodes have been modified with different substances such as gold/gold nanoparticles , graphene , polypyrrole , bioreceptors and carbon nanotubes with the aim of improving the analytical performance of the method. The ability of an electrode to selectively detect a specific target of concern plays an important role in detection.…”
Section: Introductionmentioning
confidence: 99%
“…16 Cyclodextrin is a cyclic polysaccharide capable of forming host-guest inclusion complexes with appropriately sized hydrophobic molecules or even nanomaterials in aqueous solution. [17][18][19][20][21] carboxymethylated beta-cyclodextrin (CM-b-CD) also has these functions, and its water solubility is greatly improved compared to its unsubstituted analogues. It is utilized as a nano-platform to carry various materials, which can improve the solubility and stability of functional molecules, and also play a sustained release effect.…”
Section: Introductionmentioning
confidence: 99%